Numerical modelling of cold-formed steel single C-section portal frames. (July 2019) - Rinchen,; Rasmussen, Kim J.R.
Abstract: This paper presents a comprehensive investigation of the numerical modelling of cold-formed steel single C-section portal frames using shell elements. The model accounts for the semi-rigid behaviour of connections using mesh-independent point-based fasteners at the location of physical bolts. The behaviour of deformable fasteners is ascribed though the use of connector sections. Nonlinear analysis is carried out to obtain the load-displacement response leading to the prediction of frame strength. The predicted strengths of frames are compared with experimental results. The main cause of the observed flexural-torsional buckling behaviour of frames is highlighted and the importance of using an accurate fastener model is emphasized. Highlights: Numerical modelling of cold-formed steel (CFS) single C-section portal frames using shell elements is presented. The successful use of mesh-independent fasteners with connector sections for modelling bolted connection is demonstrated. The behaviour and capacities of CFS portal frames predicted by advanced analysis are shown to agree with test results. The main cause of observed flexural-torsional buckling behaviour in CFS single C-section portal frames is explored.